Social distancing, politics, and wealth - Ansell, B; Cansunar, A; Elkjaer, M (Taylor and Francis, 2021)
Since the beginning of the COVID-19 epidemic, governments across Europe have attempted to prevent the spread of the disease by limiting the movement of their citizens. In this article, we analyse whether the level of compliance with social distancing measures is associated with political, economic, and demographic factors. In particular, our interests lie in two areas. First, as lockdowns have dragged on, many countries see some political resistance, often, though not always, from populist movements: are localities that support populist movements more likely to ignore social distancing measures? Secondly, economic security: do localities with higher levels of income and wealth have higher levels of social distancing? We combine anonymised movement data from people’s mobile phones drawn from the Google Community Mobility surveys with subnational economic and demographic data to answer these questions. It is found that across Europe, social distancing patterns correlate strongly with populist attitudes and economic security.